Comparative Characteristics of Protective Effect of Cryocord-S and â€œBiotrytâ€ Preparations at Pathology Prophylaxis of Liver and Organs of Reproductive System - Mozgovoj, Yu. S.; Beregovaya, Yu. P.; Lipina, O. V. (Problems of Cryobiology and Cryomedicine, 2003)
We have studied a protective effect of cord blood serum (Cryocord-S) and natural adaptogen Biotryt on the morphology of liver and reproductive system organs under long-term effect of oil-processing. Oil-processing products were proved to cause the manifested morphological changes in ratâ€™s liver and ovaries, as well as moderately manifested ones in uterus and oviducts. Cryocord-S and Biotryt adaptogen were showed to manifest a protective effect on liver and organs of reproductive system. Cryocord-S protective effect is more manifested, that allows its recommending for rehabilitation during reproductive health disorders in working women, being in a long-term contact with oil-processing products.